The impact of INH-alpha (rs12720062 G/A) gene polymorphism and serum vitamin D level on risk of premature ovarian failure - Durar Kamil Jabbar; Noor M. Ali; Hala Abdul qadir (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: The loss of ovarian function before the age of 40 is referred to as premature ovarian failure (POF). Genetic conditions and some acquired conditions may be to blame for premature ovarian failure. Vitamin D deficiency has been linked to a number of medical conditions and recent data suggest a link between premature ovarian failure and this deficiency; however, clear consensus among authors does not exist. Genetic wise, a link between premature ovarian failure and INH-alpha (rs12720062 G/A) gene polymorphism is shown by some authors. Aim of the study: To investigate the impact of inhibin alpha gene polymorphism and serum vitamin D level to risk of premature ovarian failure. Patients and methods: The study included forty women with signs and symptoms of POF and forty fertile and healthy women to represent the control group. Patients and control individuals were collected from three fertility units in Iraq, Um-Albaneen fertility center in Al-Imamain Al-Kadhimain Madical City - Baghdad, Higher Institute of Infertility Diagnosis and Assisted Reproductive Techniques - Baghdad, and from the infertility unit in Women’s and children’s hospital at Al-Diwaniyah city. Samples collection was performed during the period extended from August 2021 to September 2022. Serum vitamin D level was measured by finecare and serum inhibin was measured by ELISA. Genetic study of INH-alpha (rs12720062 G/A) genotypes and alleles was done. Results: Average vitamin D serum level of POF category was lower significantly than that of control group, 15.17 ±3.82 ng/ml versus 40.68 ±5.76 ng/ml, respectively (p < 0.001). In addition, mean Inhibin-Alpha of POF was significantly lower than that of group of controls, 3.27 ±1.28 (pg/ml) versus 29.13 ±9.11 (pg/ml), respectively (p < 0.001). Concerning INH-alpha (rs12720062 G/A) gene polymorphism, GA genotype was significantly less associated with POF in comparison with control group (p = 0.014); the odds ratio was 0.23; the wild homozygous GG genotype revealed significant association with POF, 34 versus 23, respectively (p = 0.007) and the odds ratio was 4.19. Allele G was more significantly associated with POF in comparison with control group; allele A was less significantly associated with POF in comparison with control group (p = 0.005). Conclusion: Premature ovarian failure is significantly predisposed by INH-alpha (rs12720062 G/A) genotypes and alleles and it is linked pathogenetically vitamin D deficiency and low serum inhibin level.